Ventilator Associated Pneumonia in Neonates: Do the Body Positions Really Have a Role in Prevention - Qurrat-Ul-Ann, Alia Halim, Muhammad Hayat Khan, Syeda Shireen Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ventilator associated pneumonia (VAP) is a relatively common and sometimes deadly complication of mechanical ventilation seen in neonatal ICUs around the globe. Objective: The study aimed to analyze the effect of three different infant positions on the rate of ventilator associated pneumonia in newborns in NICU. And compare the bacterial growth on tracheal aspirates in all three groups. Study design: It was randomized controlled trial study conducted for the duration of six months from 1st January 2021 to 30th June 2021 at Neonatal ICU department of Children Hospital PIMS, Islamabad. Material and Methods: The sample size was calculated by WHO sample size calculator, with power of test 80% and level of confidence 05%. Population proportion for group 1 was 67% (rate of bacterial colonization in supine group). Population proportion for group 2 was 47% (rate of bacterial colonization in lateral group). Sample size was turned out to be 50 in each group and a total of 150 patients were included in the study. The patients were randomized to one of the three groups using lottery method. The ethical and review board committee of the hospital approved the study. Results: First group patients were in supine position after the procedure of endotracheal intubation on the ventilator. The second group was the one in which infants were put in prone position by following protocol. And the third group contained patients in lateral positions. The goal of the study was to study the effect of these three positions on the incidence of ventilator associated pneumonia in case of infants admitted in hospital. The other goal was to do a comparison on the bacterial growth produced on tracheal aspirates in case of all these groups. Infants were kept in these positions and there was no information collected for 10 minutes as there could be any potential instability in respiration. After the patients were stable data was collected. Conclusion: There was no difference found in the incidence of VAP in case of all three positions and the bacterial colonization was found to be increased in case of supine position as compared to other groups. Keywords: Ventilator associated pneumonia (VAP), Neonatal ICUs, Respiratory tract.